Hypofractionated radiotherapy of breast carcinoma Hypofraktionierte Bestrahlung des Mammakarzinoms - Combs, Stephanie E. (Best Practice Onkologie, 2017)
Breast cancer is the most common cancer among women with an incidence of 70,000 new cases a year in Germany. Radiation therapy is an integral part of the multidisciplinary treatment, both in breast-conserving therapy and in special cases after mastectomy. Over the years, various radiation therapy concepts have been established, all of which have their importance depending on a variety of clinical factors. Radiation therapy can be applied normofractioned or hypofractionated. To date, four randomized studies have been conducted on the efficacy of hypofraction: the Royal Marsden Hospital/Gloucestershire Oncology Center (RMH/GOC) study; the “UK Standardisation of Breast Radiotherapy (START)” START A and START B studies, and the Canadian study. In summary, 7095 patients were treated within these studies, 89.8% with tumors below 3 cm, and 79% with negative lymph nodes. Only a minority has been treated with chemotherapy, so there is practically no experience of using taxanes in combination with hypofractionation. All studies have seen no differences between normofractionation and hypofractionation in local tumor control as well as in late sequelae. The hypofractionated whole breast radiotherapy appears not to be inferior in the local control and side-effects rate to the normofractionated radiotherapy and is now recommended in the German guidelines. However, the above-mentioned points are not yet fully answered and should be discussed individually with each patient, since radiotherapy is an individualized treatment.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Breast neoplasms; Hypofractionation; Mastectomy; Radiotherapy; Taxoides